Age-Related Increases in Benign Paroxysmal Positional Vertigo Are Reversed in Women Taking Estrogen Replacement Therapy: A Population-Based Study in Taiwan - Liu, Ding-Hao; Kuo, Chia-Hua; Wang, Chia-To; Chiu, Ch-Chih; Chen, Tzeng-Ji; Hwang, De-Kuang; Kao, Chung-Lan (Frontiers in Aging Neuroscience, 2017)
Benign paroxysmal positional vertigo (BPPV) is the most common cause of peripheral vertigo. Numerous investigations have reported an increased BPPV incidence in females and in the aged population. The hormonal characteristics of BPPV patients have not been previously investigated. This study aimed to determine the risk of BPPV in relation to menopause in a population-based study. Materials and Methods This retrospective population-based study was designed to use a nationwide longitudinal health insurance database to follow and analyze the incidence of and protective factors against BPPV in a Taiwanese population. Data Analyses Univariate and multivariate analyses were performed to calculate the adjusted hazard ratio (aHR) for the incidence of BPPV using Cox-proportional regression models. Results In the multivariate analyses, we found that older people (older than 65 years old) were more prone to develop BPPV (aHR: 5.37, 95% CI; 4.83-5.97, p<0.001). The risk of BPPV was analyzed in two specific age subgroups of elderly females. Results revealed that in both age groups (45-65 years old and >65 years old), patients who took estrogen for menopausal syndromes had a significantly lower incidence of BPPV (aHR; 0.01, 95% CI:0.06-0.23, p<0.001). Conclusion Our study provides a novel etiology and possible treatment method for the prevention of BPPV. Further studies may focus on the pathophysiological mechanism of estrogen in BPPV patients and the development of new drugs for the prevention and treatment of BPPV.